Evolution & Growth of Judicial Activism in India - Tripathy, Anwesha; Mishra, Amrita (International Journal of Psychosocial Rehabilitation, 2019)
Judicial activism does not have a limited scope. It is used to look into the issues and to enforce what benefits the community as a whole. There is no end to the word "JUSTICE," which critically says justice is for all,’ rich or poor, strong or weak,’ even karma has entrusted the king and queen with justice. The present research paper focuses on method of expansion of judicial activism in Indian democracy. India’s judicial activism had reached almost every aspect of life to ensure social justice. Majority of time the judicial review and judicial activism act as a boon for the weaker section of society in protecting their rights by simply filling out a litigation of social interest or a litigation of public interest. Several times judicial interference in executive and legislative matters has given society the upper hand in seeking justice. Judicial system is a means of providing ’ JUSTICE ’ to all, and of taking all necessary and practicable steps to protect JUSTICE’s interests. Legal framework for judicial activism in the integration of Indian constitution towards fundamental rights.